2012
DOI: 10.3109/14992027.2012.658971
|View full text |Cite
|
Sign up to set email alerts
|

The objective-subjective assessment of noise: Young adults can estimate loudness of events and lifestyle noise

Abstract: Results suggest that individuals can make a reasonable estimate of the loudness of events they experience and the overall level of noise they experience. These results may have significant influence for those interested in producing effective hearing health awareness programs in that individuals may be capable of assessing their own degree of hazard exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(66 citation statements)
references
References 8 publications
3
59
1
3
Order By: Relevance
“…Second, the estimation of leisure noise exposure might be affected by measurement errors, that is, the self-reported time of attendance to several leisure activities might be imprecise and no actual loudness measurements were performed to calculate the A-weighted equivalent levels. However, previous research showed that subjects can make a reasonable estimate of the loudness of activities they participated in,[51] which makes it possible to detect the activities with the highest risk of excessive noise levels. Third, TEOAEs and DPOAEs were evaluated in terms of their presence/absence, which might be insufficient to reveal significant relations.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the estimation of leisure noise exposure might be affected by measurement errors, that is, the self-reported time of attendance to several leisure activities might be imprecise and no actual loudness measurements were performed to calculate the A-weighted equivalent levels. However, previous research showed that subjects can make a reasonable estimate of the loudness of activities they participated in,[51] which makes it possible to detect the activities with the highest risk of excessive noise levels. Third, TEOAEs and DPOAEs were evaluated in terms of their presence/absence, which might be insufficient to reveal significant relations.…”
Section: Discussionmentioning
confidence: 99%
“…Since noise is self‐reported, it is impossible to determine the degree to which it approximates objective levels of noise or idiosyncratic noise sensitivity. However, it should also be noted that studies have shown a strong association between self‐rated noise and objective measures of noise (Beach et al ). Another potential limitation of the data is that since self‐rated noise is undifferentiated, the variable captures both indoor and outdoor noise, and thus it is impossible to estimate the proportion that is attributable to land use exposure out of the total noise experienced.…”
Section: Discussionmentioning
confidence: 99%
“…El uso de datos autoinformados en diferentes actividades y situaciones de la vida cotidiana podría contener sesgos de exageración o de memoria selectiva. Sin embargo, hay estudios 35,36 que demuestran que las personas pueden hacer una estimación razonable de la intensidad de los eventos y nivel general de ruido que experimentan, al existir una correlación significativa entre las estimaciones subjetivas del individuo sobre su exposición general al ruido (mediante cuestionarios) y la exposición media diaria real al ruido (medida objetivamente a través de dosimetría). En todo caso, se demandan cuestionarios adaptados y validados para la población trabajadora que midan intensidad y tiempo de exposición a fuentes de ruido de la vida cotidiana.…”
Section: Discussionunclassified